Method and Motives for Naming Geographical Objects in Chinese and Western Cultures - LIU, LU; RYBAKOV, MIKHAIL A. (The journal of contemporary issues in business and government, 2021)
Place name is a symbol to describe geographic object. With the development and change of history, place name gradually gets strong national cultural characteristics. Comparing Chinese and Western place names, one can found that Chinese place names pay more attention to history and culture, while Western place names are more functional and pay more attention to rationality and practicality. This is related to the different historical and cultural backgrounds and national cultural psychology between China and the West.